The Determinants of Cocoa Competitiveness in West Sulawesi Province - Mas’ud, Anis Anshari; Adha, Wahyu Maulid; Erwin, Erwin (AIBPM Publisher, 2024)
Cocoa processed products represent a significant proportion of the output of the plantation subsector in West Sulawesi Province, Indonesia. The West Sulawesi Provincial Government continues to encourage an increase in cocoa production. This is done as a form of government commitment to the potential of cocoa products, which are the mainstay of the region. It is therefore important to identify the factors that influence the increased competitiveness of processed cocoa products. The objective of this research is to ascertain the factors that influence the enhancement of competitiveness by utilising internal dimensions to assess competitiveness. There are three principal dimensions that are widely acknowledged: human resource competence, product excellence, and technological innovation. This research employs both primary and secondary data obtained directly from cocoa product businesses in West Sulawesi Province. The data is then analysed using SEM from the PLS 3.0 application.